UNDERGROUND FOREST: INOVASI HUTAN BAWAH TANAH SEBAGAI SOLUSI PENCEMARAN UDARA DAN BANJIR IBUKOTA JAKARTA TAHUN 2025 - Masliana, Masliana; Anjarwati, Hestin Dwi; Ruhana, Umi Tri; Rahmawati, Dian Astri; Rachman, Wildan Ari (Program Kreativitas Mahasiswa - Gagasan Tertulis, 2014)
Flooding and pollution are serious problem for metropolitan cities like Jakarta. Population density in Jakarta is considered as the second cause of the problem and the wrong attitude like habit of throwing garbage in rivers that triggered the closure irrigation and the use of fossil fuels for transportation and pollution of industry causing global warming. Urban forest planting is still minimal compared to the level of air pollution in Jakarta. Planting city forests requires large area, so we offer a new concept of urban forest that is effective and efficient place so it will not reduce development and community activities metropolitan. Underground Forest made by utilizing the concept of forest land for the construction of the underground by utilizing watershed and catchment water for hydroelectric energy and water uptake artificial lighting is collected in artificial lake, so to addressing the problem of air pollution are also addressing the problem of flooding. This forest is a commercial forest which has a production forest, forest Trembesi also has more economic value in terms of tourism.Keywords: City Forest, water power, artificial lake, commercial Forest